EFFECT OF ADDITION BAKING POWDER AND WATER ON SENSORY AND PHYSICAL CHARACTERISTICS OF MOCAF(Modified Cassava Flour) BISCUITS - Wuri Marsigit; Bonodikun Bonodikun; Lortina Sitanggang (Jurnal Agroindustri, 2017)
The purposes of this study were to reveal   the effect of addition of baking powder and water on sensory characteristics (color, flavor, aroma and texture) and physical characteristics (expending, porosity,  and  water  content)  and  also  value-added    biscuit  from  Mocaf.  This  research  was conducted in Agricultural Technology Laboratory, Faculty of Agriculture, University of Bengkulu The experimental design used was complete random sampling ith two factors included percentage addition of baking powder  (0.2 %, 0.4 % and 0.6 %) and percentage addition of watwr (2 %, 6 % and 10 %), so it can be consisted of 9 treatment combination. Data were analyzed with ANOVA by using SPSS 17.0. Data were presented in the form of tabel. Result of study found that there were significant effects of addition baking powder dan water proportion on sensories and physics characteristic of mocaf biscuits. Biscuits mocaf  was  most preferred by the panelists (color, aroma and taste) were biscuit with addition of 10% water and 0.6 % baking powder, with physic characteristics expanding (56.55%), porosity (60,44) and water content (3.97%). The value-added biscuit mocaf were Rp 2,432 per 100 gram.